2021
DOI: 10.3390/horticulturae7110509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated CO2 and Temperature on Growth, Development and Nutrient Uptake of Tomato

Abstract: Elevated carbon dioxide (EC) can increase the growth and development of different C3 fruit crops, which may further increase the nutrient demand by the accumulated biomass. In this context, the current investigation was conceptualized to evaluate the growth performance and nutrient uptake by tomato plants under elevated CO2 (EC700 and EC550 ppm) and temperature (+2 °C) in comparison to ambient conditions. Significant improvement in the growth indicating parameters like leaf area, leaf area index, leaf area dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…High leaf area leads to higher biomass (fresh weight and dry weight) accumulation upon elevated CO 2 treatment, this may be due to the high rate of photosynthesis and water use efficiency under elevated CO 2 condition. Improvement in leaf area and LAI was recorded (Rangaswamy et al, 2021), at both elevated levels of CO 2 . There was significantly higher total leaf area at 50% flowering in tomato.…”
Section: Grain Weight/spikementioning
confidence: 89%
“…High leaf area leads to higher biomass (fresh weight and dry weight) accumulation upon elevated CO 2 treatment, this may be due to the high rate of photosynthesis and water use efficiency under elevated CO 2 condition. Improvement in leaf area and LAI was recorded (Rangaswamy et al, 2021), at both elevated levels of CO 2 . There was significantly higher total leaf area at 50% flowering in tomato.…”
Section: Grain Weight/spikementioning
confidence: 89%
“…This method allowed for ventilation, cooling and daily management when the midday temperatures became too high. Such devices were previously tested and used in tomato [34], cucumber [35] and other crops. The solar radiation value was varied between 400 and 700 W•m −2 and the oxygen content was 21% during the treatment in the solar greenhouse.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…These studies revealed that C4 maize crop have the potential to respond positively to elevated CO 2 like C3 crops. Majority of the studies reported on individual effects of elevated carbon dioxide and temperature on phenology, physiology and biochemistry of different crops [45][46][47][48][49] . Although the combined and interactive effects of elevated CO 2 and temperature on physiology, phytochemistry, and biomass have been attempted in limited manner 36,[50][51][52] .…”
mentioning
confidence: 99%